Iron winter - Baxter, Stephen (Baxter, Stephen. Northland trilogy, 2013)
"Many generations ago, the Wall was built to hold back the sea. A simple dam, it grew into a vast linear city, home to scholars, builders, and merchants. Northland's prosperity survived wars and unrest--and brought the whole of Europe together. But now darkness is falling. Days grow shorter, temperatures colder, and in the wake of long winters come famine, destruction, and terror. As a mass exodus to warmer climes threatens to fracture Northland, one man believes he can outwit the cold, and even salvage some scraps of the great civilization--before interminable gloom settles over the land; before the fires of war lay waste to an empire; before the ice comes..."--